USAGE AND RISK PERCEPTION OF INTERNET BANKING: CASE STUDY IN YOGYAKARTA SPECIAL REGION, INDONESIA - Santoso, Singgih; Murtini, Umi (European Scientific Journal, ESJ, 2014)
With number of samples 401 respondents, research aim is to measure consumer awareness, usage, and risk perceptions towards internet banking which based on information technology and communications. Research design is survey using a questionaire with 401 respondent as a sample; sampling method is multistage random sampling in five sub-provinces in Yogyakarta Special Region Province. The result show internet banking awareness is low, namely 27,4%; level of internet banking owner much more low, namely around 3,7%. Main reason not using internet banking is about lack of consumer readiness, lack of internet knowledge, and high administration cost. Respondent that considering to know internet banking most correlating this facility with a balance and banking transaction cheque via internet. Transaction frequency for internet banking is vary, between one times in a month until more than five times in a month, with the number of transactions also vary, between Rp. 1.000.000,- Rp. 2.000.000- until above Rp. 5.000.000,-. In terms of risk perception, younger age group (18-24 years old) have the courage to take higher risk than upper age groups.